ECONOMIC MECHANISM OF OPTIMAL LOAD SHARING IN BELARUSSIAN POWER SYSTEM WITH MONOPSONY SPOT MARKET - A. M. Zaborovskiy (Наука и техника)
The economic mechanism of power source loading on the Belarusian wholesale market of electric power is developed in the paper. The mechanism is based on the electric power cost minimization for consumers but not fuel cost as it is in the current vertically-integrated structure of power industry.Price on the wholesale market will be minimal when there is an equality in marginal costs in respect of power purchase from the side of all power-generating companies, which are loaded by a market operator, with correction for transmission losses caused by loading sources of the corresponding power supply company. It is proved that optima of power source loading in the vertically-integrated and vertically-desintegrated power systems are the same in the case when there is a strategic collusion between power supply companies. A new organizational model of the Belarusian power industry with mechanisms stimulating power supply enteфrises to reduce power generation, transmission and distribution costs is considered in the paper. Proposals concerning improvement of tariffication in power industry are made in the paper.